Weight Loss and Percutaneous Endoscopic Gastrostomy Tube Placement during Chemoradiotherapy for Locally Advanced Cancer of the Oropharynx Do Not Negatively Impact Outcomes - Baine, Michael J.; Dorius, Timothy; Bennion, Nathan; Smith, Lynette; Zhen, Weining; Ganti, Apar Kishor (Frontiers in Oncology, 2017)
Objectives: Concurrent chemoradiotherapy is standard of care in locally advanced oropharyngeal cancer (LA-OPC). This treatment regimen results in significant acute toxicities. This study investigates the effect of treatment-related toxicity on patient outcomes. Methods: Patient information was retrospectively collected for patients treated for LA-OPC between 2007 and 2014. Factors analyzed included age, gender, pre-treatment ECOG performance status, smoking history, patient BMI prior to and following treatment, tumor histology, disease stage, disease recurrence, incidence and timing of feeding tube placement, radiation dose received, chemotherapy regimen used and if it was completed, and patient survival. All statistical analysis was provided through the UNMC Department of Biostatistics. Results: 74 patients were identified with a median follow-up of 3.4 years and a median age of 58.5. Most patients were male (87.8%) and had squamous cell histology (98.7%). Most patients underwent chemoradiotherapy alone (98.6%) and received concurrent cisplatin (78.4%) with approximately half (53.4%) receiving all planned chemotherapy. Upon multivariate analysis, both disease-free and overall survival rates were improved by lower pre-treatment BMI, increased weight lost during treatment, and lack of PEG tube placement prior to treatment initiation. Neither disease-free survival nor overall survival were impacted by placement of a PEG tube during active treatment. Conclusions: This data suggests that weight loss and PEG tube placement during chemoradiotherapy for LA-OPC, presumably due to treatment-associated mucositis and xerostomia, are not associated with worse outcomes.